Diet-induced obesity, gut microbiota and bone, including alveolar bone loss - Sathima Eaimworawuthikul (2018)
© 2017 Elsevier Ltd Obesity is a major risk factor for several pathologies, including jaw bone resorption. The underlying mechanisms involved in pathological conditions resulting from obesity include chronic systemic inflammation and the development of insulin resistance. Although numerous studies have indicated the importance of the role of gut microbiota in the pathogenesis of inflammation and insulin resistance in obesity, only a few studies have established a relationship between obesity, gut microbiota and status of the jaw bone. This review aims to summarize current findings relating to these issues, focusing on the role of obesity and gut microbiota on jaw bone health, including possible mechanisms which can explain this link.